MEDIA PERMAINAN KARTU HURUF DALAM PEMBELAJARAN BAHASA PADA PENDIDIKAN ANAK DI KB BAITUL ILMI SADAR SRIWIJAYA TAHUN PELAJARAN 2024/2025 - Ismatul Fadhilah; Endang Ekowati; Firmansyah (UNISAN JURNAL, 2026)
This study aims to describe the implementation of letter-card game media in language learning for early childhood students at KB Baitul Ilmi Sadar Sriwijaya in the 2024/2025 academic year. The research background is the low ability of young children in recognizing letters, distinguishing letter shapes, and identifying initial word sounds due to monotonous learning media. This study employed a descriptive qualitative method with teachers and group B students as the subjects. Data were collected through observation, interviews, documentation, and developmental assessment. Data analysis was conducted using Miles & Huberman’s model: data reduction, data display, and conclusion drawing. The findings indicate that the letter-card media significantly improves children’s language skills, particularly in letter recognition, sound pronunciation, and speaking confidence. Children became more enthusiastic, active, and engaged during learning activities, showing notable improvements in cognitive and language development. The study concludes that letter-card media is an effective and developmentally appropriate tool for early childhood language learning.